Utopia, history and prophecy: the joaquimism as philosophy for Brazil - Rossato, Noeli Dutra (Argumentos - Revista de Filosofia, 2020)
The text assumes that the conception of history from the utopian and prophetic-millenarian strands are constitutive not only of the founding myth of the Brazilian State, but also of our most authentic philosophical thought; and that, in its origins, we find the work of Abbot Joachim of Fiore (1135-1202). At first, we show that one of the expressions of the utopian aspect in our culture comes from the popular Festivities of the Empire of the Holy Spirit of Luso-Brazilian tradition that roots in medieval Joachimism. The prophetic-millenarian aspect, in turn, is part of the work of the Jesuit Antonio Vieira (1608-1679) and consolidated through the absorption of the utopian heritage of the Joaquimism, complemented by Apocalyptic and Sebastianian elements. Finally, we take a few steps from the novel A Pedra do Reino, by Ariano Suassuna (1927-2014), with, in our view, articulate the main core of the utopian dimension with the theory of the Fifth Empire and the millenarianism.